2021
DOI: 10.1001/jamacardio.2020.7308
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Neutrophil Extracellular Traps in Coronary Thrombus of a Case Series of Patients With COVID-19 and Myocardial Infarction

Abstract: IMPORTANCESevere coronavirus disease 2019 is characterized by the intense formation of neutrophil extracellular traps (NETs), leading to the occlusion of microvessels, as shown in pulmonary samples. The occurrence of ST-elevated myocardial infarction (STEMI) is a serious cardiac manifestation of COVID-19; the intrinsic mechanism of coronary thrombosis appears to still be unknown.OBJECTIVE To determine the role of NETs in coronary thrombosis in patients with COVID-19.DESIGN, SETTING, AND PARTICIPANTS This was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 13 publications
8
79
0
Order By: Relevance
“…Moreover, patient selection is in accordance with the routine clinical practice, as patients underwent thrombus aspiration based on 2017 AHA guidelines [ 36 ] and ESC 2017 [ 37 ] to manage the patient with STEMI. Accordingly, the percentage of patients undergoing thrombus aspiration in our study (176 of 474, 37%) agrees with previous and more numerous observational studies [ 36 39 ]. Another limitation of the study was the not fully evaluation of inflammatory markers as pro-inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, patient selection is in accordance with the routine clinical practice, as patients underwent thrombus aspiration based on 2017 AHA guidelines [ 36 ] and ESC 2017 [ 37 ] to manage the patient with STEMI. Accordingly, the percentage of patients undergoing thrombus aspiration in our study (176 of 474, 37%) agrees with previous and more numerous observational studies [ 36 39 ]. Another limitation of the study was the not fully evaluation of inflammatory markers as pro-inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 92%
“…Preliminary data indicate that SARS-CoV-2 can activate NETosis in human neutrophils, potentially due to increased levels of intracellular Reactive Oxygen Species (ROS) [95]. Besides thrombosis, NETosis has also been associated with ST-elevated myocardial infarction (STEMI) in COVID-19 disease [96]. All these data point to a crucial role of NET formation leading to severe pulmonary complications of COVID-19.…”
Section: Relevance Of Neutrophil Extracellular Traps In Covid-19mentioning
confidence: 99%
“…All these data point to a crucial role of NET formation leading to severe pulmonary complications of COVID-19. Based on the growing evidence about the involvement of NETs in the pathogenesis of COVID-19, NET inhibitors have been proposed and are being studied as a feasible way to prevent coronary thrombosis in patients with severe COVID-19 disease [95][96][97][98]. Several intervention trials are currently recruiting with a diversity of study designs and outcome measures.…”
Section: Relevance Of Neutrophil Extracellular Traps In Covid-19mentioning
confidence: 99%
“…34 Additionally, a small case series of COVID-19 patients undergoing primary coronary interventions for ST elevation MI showed neutrophil extracellular traps (NETs) formation in 68% of thrombi. 35 In addition to larger vessel thromboses, examination of the lung and cutaneous tissue autopsy samples from patients who died from severe COVID-19 infection and respiratory failure demonstrates the presence of microvascular injury with thrombosis. 36,37 Diffuse inflammatory alveolar change with macrophage infiltration has been reported in early pathological studies of patients with COVID-19 pneumonia, alongside extensive vascular congestion.…”
Section: Thrombotic Complications In Covid-19mentioning
confidence: 99%
“…A large study of 3334 hospitalised COVID‐19 patients demonstrated MI was the commonest thrombotic event in their cohort, occurring in 8·9% of patients 34 . Additionally, a small case series of COVID‐19 patients undergoing primary coronary interventions for ST elevation MI showed neutrophil extracellular traps (NETs) formation in 68% of thrombi 35 …”
Section: Thrombotic Complications In Covid‐19mentioning
confidence: 99%